Pelatihan Pengolahan Telur Asin dalam Meningkatkan Jiwa Entrepreneurship pada Mahasiswa Pendidikan Ekonomi - Buji, Grace Evelina; Lenlioni, Liling; Hariatama, Fendy; Sundari, Sundari; Rohaetin, Sri (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Higher education plays a strategic role in fostering students' entrepreneurial spirit to tackle global economic challenges. One solution to reduce the unemployment rate among university graduates is to equip students with entrepreneurial skills that can be directly applied. This study aims to analyze the effectiveness of salted egg processing training in enhancing the entrepreneurial mindset of Economic Education students at Palangka Raya University. The research employs a descriptive qualitative approach with data collection techniques including in- depth interviews, participatory observation, and document analysis. The findings indicate that experiential learning-based training positively impacts students' understanding, skills, and interest in entrepreneurship. Students show improvements in technical production, managerial skills, and product marketing. However, challenges in implementing the training include capital constraints and initial production experience limitations. Overall, salted egg processing training has proven effective in enhancing students' entrepreneurial skills, both technically and managerially. With adequate institutional support, this program can serve as a model for entrepreneurship development among economic education students.